Molecular and epidemiological surveillance of Plasmodium spp. during a mortality event affecting Humboldt penguins (Spheniscus humboldti) at a zoo in the UK. (December 2022) - González-Olvera, Merit; Hernandez-Colina, Arturo; Himmel, Tanja; Eckley, Lindsay; Lopez, Javier; Chantrey, Julian; Baylis, Matthew; Jackson, Andrew P.
Abstract: In 2017, a mortality event affected Humboldt penguins at Chester Zoo (UK), which coincided with the diagnosis of avian malaria (AM) in some birds. AM is found worldwide wherever a competent mosquito vector is present, but the disease is particularly severe in penguins and other species that originate from non-endemic regions. To better understand the role of AM and manage its threat to penguin collections, Plasmodium was surveyed through PCR at Chester Zoo in mosquitoes, penguins, and dead free-living wild birds during and around the mortality event. Additional sequences were obtained from penguin fatalities from four other UK zoological collections. All sequences were integrated into phylogenetic analyses to determine parasite species and lineages. In total, 753/6459 positive mosquitoes were recorded (11.7% prevalence), reaching a weekly peak of 30% prevalence in mid-summer. Among penguin fatalities at Chester Zoo, several penguins presented signs and lesions compatible with AM; nevertheless, exoerythrocytic meronts were identified in only one case and Plasmodium spp. was identified in 5/22 birds. Phylogenetic analysis revealed at least five parasite cytb lineages of three Plasmodium species ( P. matutinum, P. relictum and P. vaughani ) circulating in mosquitoes at Chester Zoo; however, infections in free-living wild birds and penguins were only from P. matutinum . Plasmodium matutinum was confirmed as the cause of death of one penguin and was highly suspected to be the cause of death of another three. The lineage LINN1 was associated with 4/5 penguin infections. AM had a key role in the penguin multicausal mortality event. Understanding the risk of AM to penguin collections at Chester Zoo and elsewhere requires long-term surveillance to examine the association between Plasmodium infection and penguin mortality and the variability in parasite virulence. Surveillance of Plasmodium spp. in mosquitoes and local birds provides information about the parasite's transmission cycle locally, and could warn about infection risks to species of interest, which is essential for efficient disease control and prevention. Graphical abstract: Image 1 Highlights: Plasmodium infection in penguins, mosquito and wild birds is described. Humboldt penguin mortality due to P. matutinum was recorded for the first time. One of three Plasmodium spp. found in mosquitoes infected penguins and wild birds. Detecting Plasmodium infections is challenging despite pathological evidence.